M95. Rare Genetic Variants and Novel Missense Coding Mutations in the Neurotrophin Signaling Pathway Genes With Focus on the Scaffold Protein ARMS/KIDINS220 and Rho-GEF TRIO Are Implicated in Psychosis Risk - Kranz, Thorsten (Schizophrenia bulletin, 2017)
Background: Multiple lines of evidence corroborate impaired signaling pathways as relevant to the underpinnings of schizophrenia. There has been an interest in neurotrophins, since they are crucial mediators of neurodevelopment and in synaptic connectivity in the adult brain. We herein report rare missense polymorphisms and novel missense mutations in neurotrophin receptor signaling pathway genes. Furthermore, we observed that several genes have a higher propensity to harbor missense coding variants than others. Methods: Case ascertainment: Cases with schizophrenia or schizoaffective disorder, age 18–55 years, were recruited from treatment settings and all provided informed consent for the study. Diagnosis was determined including Diagnostic Interview for Genetic Studies (DIGS), Family Interview for Genetic Study (FIGS), Positive and Negative Syndrome Scale (PANSS) and Wechsler Adult Intelligence Scale (WAIS-III). Early trauma exposure was assessed using the Early Trauma Inventory (ETI). Genomic DNA source and sample size: We conducted high-coverage targeted exome capture in a subset of neurotrophin genes (n = 38) in 48 comprehensively characterized cases with schizophrenia-related psychosis. Targeted exome capture: Pooled capture library was quantified by Qubit (Invitrogen) and Bioanalyzer (Agilent) and sequenced in an Illumina MiSeq sequencer using the 2 × 150 paired-end cycle protocol. Reads were aligned to the hg19 build of the human genome using BWA with duplicate removal using samtools as implemented by the Illumina MiSeq Reporter. Variant detection was performed using GATK UnifiedGenotyper. Variants were annotated with ANNOVAR annotator to cross-reference against known dbSNP, 1000 Genomes, ESP6500, COSMIC mutations and Schizophrenia Exome Sequencing Genebook entries. Results: Notably, 37 of 48 cases harbored rare missense coding polymorphisms (MAF ≤ 1%) and novel missense coding variants in at least one of the neurotrophin signaling genes. The highest burden was exhibited by the NTRK1-ARMS/Kidins220-TRIO pathway with more than 50% of all observed rare neurotrophin gene polymorphisms. The subject carrying ARMS/Kidins220 H1085R (proline rich domain) is a particular case associated with a life-long history of psychiatric problems. The gene TRIO revealed the most rare polymorphisms and a novel mutation (V2941I) in its kinase domain, which is known to interact with the p75 receptor. ARMS/KIDINS220 and TRIO are involved in spine formation and elimination. Conclusion: Accumulation of rare variants and novel mutations in neurotrophin signaling pathways and especially the scaffold protein ARMS/KIDINS and the RHO-GEF TRIO offer a mechanistic entry point how neuronal networks in schizophrenia cases are affected. Further evidence is given by immunostaining of primary cortical cultures comparing wild type and mutant protein localization. ARMS and TRIO mutant proteins are retained in the soma.